How to Develop Marketing Strategy, Packaging Designs, and Superior Product Processing Education? - Wulandari, Astri; Marcelino, Dandy; Suryawardani, Bethani; Gusnadi, Dendi; Prabawa, Bijaksana; Arumsari, Rizki Yantami (Jurnal Penyuluhan, 2024)
Produce such as fruits and vegetables have the production potential on an industrial scale with a low price. Most residents in Sukawarna work as farmers of fruits, horticultural crops and vegetables. Farmers sell raw fruit and vegetable products without diversification. To compete with other economic actors, the government, community, and universities must support the development of high-quality commodity products. However, the community still faces some challenges, particularly their skills or expertise, but in this era, the main issues are knowledge when facing change (transformation) and a lack of creativity in managing superior product commodities to increase sales. The aim of this study is to help economic business actors in Sukawarna develop competitive knowledge and skills by referring to the partners’ situation and issues. Community empowerment program facilitators were involved to conduct a participatory action research. It was found that there were several partner problem solutions. The first is the training of the economic actors in Sukawarna on how to manage raw commodity products into processed products with added value. Next is marketing assistance to help partners process vegetables from Sukawarna’s main commodity through accurate marketing strategy in communicating the processed product. The last solution is the use of attractive packaging designs and product labels for processed main commodities in Sukawarna to attract potential consumers. The study results recommend the following: an educational program for the transformation of superior commodities into ready-to-use processed products, assistance with marketing strategies, and designing packaging and product labels to market the processed commodities.